23‐2: 2351‐ppi OLED Display with Stacked OS‐FETs with L = 0.36 µm. Issue 1 (29th May 2019) - Shishido, Hideaki; Kimura, Kiyotaka; Nomura, Masumi; Hirose, Takeya; Kato, Sho; Aoyama, Tomoya; Nomura, Shiho; Nei, Kosei; Okazaki, Yutaka; Ikeda, Takayuki; Yamazaki, Shunpei
Abstract : A 2351‐ppi organic light‐emitting diode (OLED) display incorporating memories in pixels is proposed. Each pixel contains stacked oxide semiconductor (OS) field‐effect transistors (FETs) (with a channel length of 0.36 μm), which are used to create the memory in the pixel.